2018
DOI: 10.1002/ccr3.1917
|View full text |Cite
|
Sign up to set email alerts
|

Use of direct oral anticoagulants in the treatment of left ventricular thrombi: A tertiary center experience and review of the literature

Abstract: Key Clinical Message Direct oral anticoagulants can potentially provide a more convenient oral alternative for the management of left ventricular thrombi than Warfarin. These medications do not require frequent monitoring and have less drug‐drug interactions. Randomized controlled trials are needed to further demonstrate their efficacy and safety in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
(57 reference statements)
0
26
0
Order By: Relevance
“…Previously, evidence for the use of DOACs in the setting of LVT have been confined to case reports and case series, and there remain limited comparative studies of DOACs versus VKA. 16 -29…”
Section: Introductionmentioning
confidence: 99%
“…Previously, evidence for the use of DOACs in the setting of LVT have been confined to case reports and case series, and there remain limited comparative studies of DOACs versus VKA. 16 -29…”
Section: Introductionmentioning
confidence: 99%
“…The American College of Cardiology (ACC) has presented TTE as the screening modality of choice in patients presumed to have LVT, as performed in our patient. The pathophysiology of LVT formation is similar to other causes of thrombi formation, and can be explained by Virchow's triad: hypercoagulable state, stasis, and endothelial injury in addition to a low ejection fraction seen after a MI [8]. LV apical thrombi have also been associated with systemic thromboembolic events such as stroke leading to significant morbidity and mortality [5].…”
Section: Discussionmentioning
confidence: 95%
“…The management of LVT and associated embolization has been actively debated due to lack of randomized clinical control trials [8,10]. A cross-sectional study evaluating 35 patients with LV apical thrombi determined that the LVT resolved in all patients being treated with aspirin and warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…Our cases are supported by multiple published articles providing evidence on the efficacy of DOACs in the treatment of intracardiac thrombosis . Shokr et al 16 demonstrated multiple cases revealing the resolution of LV thrombus with apixaban and rivaroxaban. Several case reports have been published on LV thrombus secondary to tachycardia-induced and hypertrophic cardiomyopathies that have been treated with DOACs.…”
Section: Discussionmentioning
confidence: 99%